2024
DOI: 10.2147/oarrr.s441720
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Lung Ultrasound as a Method for Early Diagnosis of Interstitial Lung Disease in Patients with Rheumatoid Arthritis

Pedro Santos-Moreno,
Maria Fernanda Linares-Contreras,
Gabriel-Santiago Rodríguez-Vargas
et al.

Abstract: Purpose To determine the value of lung ultrasound (LUS) compared to high-resolution computed tomography (HRCT) in the early diagnosis of interstitial lung disease (ILD) in patients with rheumatoid arthritis (RA). Patients and Methods An observational prospective study was performed. Were included patients with respiratory symptoms or/and, patients with crackles in auscultation during medical consultation. All patients underwent to chest X-rays, LUS, HRCT,and respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Our cross-sectional study found parenchymal abnormalities in LUS in almost half of low symptomatic RA patients, similar to two recent studies by Santos Moreno and Otaola et al that described the narrow base reverberation (B lines) in a high percentage in RA-ILD [33,49], also in the early phase of disease [33].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our cross-sectional study found parenchymal abnormalities in LUS in almost half of low symptomatic RA patients, similar to two recent studies by Santos Moreno and Otaola et al that described the narrow base reverberation (B lines) in a high percentage in RA-ILD [33,49], also in the early phase of disease [33].…”
Section: Discussionsupporting
confidence: 92%
“…Even if air is not a favorable medium for transmission of LUS waves, the identification of vertical comet artifacts (B lines, due to fluid and collagen accumulation) and pleura layer morphological abnormalities has shown good sensitivity and concordance with the extent and severity of ILD in HRCT in autoimmune diseases and RA [ 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%